“To Thee Do We Send Up Our Sighs”: Documenting Twentieth-Century Marian Shrines in the Republic of Ireland - Campbell, Eve (Journal of Contemporary Archaeology, 2020)
Public Marian shrines are a ubiquitous element of rural and urban landscapes in the Republic of Ireland. Largely dating from the mid-twentieth century, the monuments formed part of a broader process of reconfiguring the Irish landscape in the post-Independence period. In this photo essay I explore the monuments, reflecting on how they served to articulate restrictive gender norms influenced by nationalist discourse and Catholic teaching. I also look at contemporary material practices associated with the shrines and their role in more vernacular forms of Marian devotion outside the tightly regulated space of the Catholic Church.